2017
DOI: 10.1038/s41598-017-09133-0
|View full text |Cite
|
Sign up to set email alerts
|

Deep time perspective on turtle neck evolution: chasing the Hox code by vertebral morphology

Abstract: The unparalleled ability of turtle neck retraction is possible in three different modes, which characterize stem turtles, living side-necked (Pleurodira), and hidden-necked (Cryptodira) turtles, respectively. Despite the conservatism in vertebral count among turtles, there is significant functional and morphological regionalization in the cervical vertebral column. Since Hox genes play a fundamental role in determining the differentiation in vertebra morphology and based on our reconstruction of evolutionary g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 78 publications
(145 reference statements)
0
19
0
Order By: Relevance
“…Interestingly, in the same study, Böhmer and Werneburg [2017] reported that in crocodiles, Hoxa5 is expressed at CV9, whereas in P. sinensis , it is expressed at CV2. This anterior expression in the turtle seems to be related to the absence of free cervical ribs, which allows the turtle to retract the head and neck inside the shell.…”
Section: Hox Genes In Reptile Developmentmentioning
confidence: 94%
See 2 more Smart Citations
“…Interestingly, in the same study, Böhmer and Werneburg [2017] reported that in crocodiles, Hoxa5 is expressed at CV9, whereas in P. sinensis , it is expressed at CV2. This anterior expression in the turtle seems to be related to the absence of free cervical ribs, which allows the turtle to retract the head and neck inside the shell.…”
Section: Hox Genes In Reptile Developmentmentioning
confidence: 94%
“…More recently, Böhmer and Werneburg [2017] suggested that expression of Hoxc6 (at the cervicothoracic transition) corresponds to the lack of ventral ribs in turtles, since it is expressed in prevertebrae and future carapacial dermis, but not in the somatopleure (region in which ventral ribs are missing). The authors also suggested that Hoxa7 was recruited for a turtle-specific function because most turtles possess a highly retractile neck that requires specialization at CV8.…”
Section: Hox Genes and The Formation Of The Turtle Shellmentioning
confidence: 99%
See 1 more Smart Citation
“…Olivier Rieppel (2013) The shell, the toothless jaws with beaks and the clumsy and slow locomotion, even from the outside, make turtles "one of nature's most immediately recognizable life forms" (Adler 2007). From "the inside", they may look even more different: their unfenestrated skulls (unique among extant reptiles; Ferreira & Werneburg 2019; Chapter 2 of this thesis), their extremely mobile necks (Werneburg et al 2015a), the anatomical composition of the carapace and plastron (Nagashima et al 2009), their scapular and pelvic girdles inside the thoracic cage (Lyson & Joyce 2012), and their highly conserved cervical and trunk vertebral count (Böhmer & Werneburg 2017) are but a few of the morphological modifications of turtles that makes them one of the most intriguing vertebrate groups from a macroevolutionary perspective. At the same time that their very unique morphology leaves no room for doubts on their monophyly, it also makes it difficult to establish homologies with other reptiles (Carroll 2013), hampering the assessment of the group's origin and making the phylogenetic origin of turtles one of the oldest debates in vertebrate paleontology, lasting for more than 200 years (Rieppel 2013(Rieppel , 2017.…”
Section: Turtles As Models Of Vertebrate Evolutionmentioning
confidence: 99%
“…Its appearance completely reorganized the ancestral reptilian body plan in this lineage, not only modifying the ribs and dorsal vertebrae, but also completely reorganizing the whole turtle body. The musculoskeletal alterations related to the encapsulation of the scapular girdle and extensive reorganization of musculature related to the limb muscles (explained by the hypothesis of folding of the lateral body wall ;Nagashima et al 2009Nagashima et al , 2012Kuratani et al 2011), the division of function between the hypaxial muscles and the dorsal ribs that led to the development of their unique ventilatory system , the constraint on the number of cervical and thoracic vertebrae (Böhmer & Werneburg 2017), and even modifications on the skull, such as the emarginations (Werneburg 2015), mode of palatoquadrate fixation (Werneburg & Maier 2019), and the skull architecture (Chapter 5 of this Thesis) are thought to be related to the emergence of the turtle shell. A detailed review of the skull morphology, development and its modifications from a reptilian body plan are discussed in Chapter 2 of this thesis.…”
Section: Turtles As Models Of Vertebrate Evolutionmentioning
confidence: 99%